2010
DOI: 10.1007/s12272-010-0620-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of paeoniflorin on LPS-induced liver inflammatory reactions

Abstract: Paeoniflorin (PF), a monoterpene glucoside, is a primary bioactive component of paeony, the root extract of Paeonia lactiflora. We tested the antioxidant effects of PF and its ability to prevent lipopolysaccharide (LPS)-induced oxidative stress. We intraperitoneally administered PF (2.5, 5, or 10 mg/kg) to rats for 20 days. On day 21, we injected the rats with LPS 4 h before sacrifice and measured serum levels of glutamate oxaloacetate transaminase, glutamate pyruvate transaminase, lactate dehydrogenase as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…Paeoniflorin (Pae), a monoterpene glucoside, is one of the principal bioactive components of total glucosides of paeony (TGP) extracted from the root of Paeonia lactiflora. Pae has been verified to have anti-inflammatory (Fu et al, 2009;Jiang et al, 2009a,b;Huang et al, 2010;Kim and Ha, 2010;Tang et al, 2010;Cao et al, 2011), anti-allergic (Lee et al, 2008), analgesic , immunoregulatory (Hsu et al, 1997;Jiang et al, 2009a,b), neuroprotective (Cao et al, 2010;Mao et al, 2011) and antitumor effects . In addition, Pae was reported to induce the immune tolerance of mesenteric lymph node lymphocytes, apoptosis of T cells (Tsuboi et al, 2004), neuroprotection in cerebral ischemia (Liu et al, 2005a,b), and enhancement of cognition (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin (Pae), a monoterpene glucoside, is one of the principal bioactive components of total glucosides of paeony (TGP) extracted from the root of Paeonia lactiflora. Pae has been verified to have anti-inflammatory (Fu et al, 2009;Jiang et al, 2009a,b;Huang et al, 2010;Kim and Ha, 2010;Tang et al, 2010;Cao et al, 2011), anti-allergic (Lee et al, 2008), analgesic , immunoregulatory (Hsu et al, 1997;Jiang et al, 2009a,b), neuroprotective (Cao et al, 2010;Mao et al, 2011) and antitumor effects . In addition, Pae was reported to induce the immune tolerance of mesenteric lymph node lymphocytes, apoptosis of T cells (Tsuboi et al, 2004), neuroprotection in cerebral ischemia (Liu et al, 2005a,b), and enhancement of cognition (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies also demonstrated the protective effects of paeoniflorin against hydrogen peroxide (H 2 O 2 )-induced oxidative damage in human umbilical vein endothelial cells (HUVECs) by decreasing the production of intracellular reactive oxygen species and increasing the production of endogenous antioxidants [33]. The antioxidative effect of paeoniflorin on the LPS-induced liver inflammatory reactions was confirmed by in vivo studies [34]. The LPS-induced decreases in antioxidant levels of superoxide dismutase, catalase, and glutathione peroxidase could be reversed by paeoniflorin [34].…”
Section: Inhibitory Effect On the Production Of Nitric Oxide And Antimentioning
confidence: 85%
“…The antioxidative effect of paeoniflorin on the LPS-induced liver inflammatory reactions was confirmed by in vivo studies [34]. The LPS-induced decreases in antioxidant levels of superoxide dismutase, catalase, and glutathione peroxidase could be reversed by paeoniflorin [34]. Inflammation induces oxidative stress by producing oxidants like reactive oxygen species and nitric oxide.…”
Section: Inhibitory Effect On the Production Of Nitric Oxide And Antimentioning
confidence: 92%
“…There is accumulating evidence that the administration of paeoniflorin (PF) can provide anti-inflammatory effects in a variety of animal models [8,12]. In the present study, we explored the protective effect of PF on ALI induced by intratracheal instillation of LPS in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin (PF), the major active constituent of TGP, has been reported to have many pharmacological effects, such as antiallergic [7], antiarthritic [8], hepatoprotective [9], and analgesic [10]. Recently, it was documented to be able to inhibit the properties systemic inflammatory responses in cecal ligation and puncture-induced sepsis [11], a main reason for ALI, protect against lipopolysaccharide (LPS)-induced liver inflammation, and prevent the adhesion between LPS-induced inflammatory endothelial cells and leukocytes [12,13]. Furthermore, it was proven to exhibit inhibitory effects on neuroinflammation, and analgesic effects through activating adenosine A1 receptor [14,15], which is beneficial for reducing PMN cell trafficking and microvascular permeability in LPS-induced lung injury [3].…”
Section: Introductionmentioning
confidence: 99%